The benefits of the task for the delivery of negative feedback - Comer, Cheryl L. (Kansas State University, 2007)
Over 50 years of research has supported the positive relationship between feedback and performance improvement. A recent meta-analysis suggests that feedback may not be beneficial for performance, and that it may actually be harmful for performance (Kluger & DeNisi, 1996). This study suggests that these inconsistencies exist because positive and negative feedback are treated like opposite sides of the same scale. In reality, positive and negative feedback are two very different types of information and should be treated differently. Current research examines feedback delivered interpersonally. When delivering feedback this way, positive feedback is often accepted while negative feedback is rejected. The current study states that alternate delivery methods may be better for the acceptance and use of negative feedback. It is suggested that negative feedback received directly from the task itself may be more accepted, more intrinsically motivating, and result in less negative emotion for receivers than negative feedback from interpersonal sources. Two hundred and two university students participated in a simple computer simulation task. They received feedback regarding their performance and then participated in the task a second time. Results revealed no differences between conditions in acceptance, possibly a result of task. When receiving negative feedback from the task, participants experienced greater intrinsic motivation than when receiving negative feedback from interpersonal sources. Finally, negative feedback from the task resulted in less negative emotion than negative feedback from interpersonal sources. By removing the interpersonal interaction, the task removes a great deal of negative emotion associated with the supervisor. This study revealed great potential for the task as a source of negative feedback. Although the workforce may not be ready for a full task-feedback system, it may serve as a good supplement for interpersonal feedback and worthy of future research in the field setting.
Keywords: Negative feedback; Feedback; Delivery; Task; Interpersonal; Computer simulation; Microworld; Psychology, General (0621); Psychology, Industrial (0624)